Preliminary Research on Longtail Shad Food in Bengkalis Riau Waters - Thamrin Thamrin (Riau University, 2021)
Longtail Shad are endemic in the waters of Riau and especially in the waters of Bengkalis Regency and have omnivore characteristics, namely eating plants and also from groups of animals. The purpose of this study is whether fish is the best in choosing food depending on the type of food or not. This study uses a survey method, which was conducted in Bengkalis waters from May to June 2019. In this study, it was shown that fish is the best in choosing food depending on the type of food available (selective), so that if the type of animal, in this case, is crustacean and crab. There are a lot of small crabs, then the worst fish eat the group of crustaceans and small crabs. However, if what is available is only from the algae group, the best fish will only eat from the algae group. So that in the stomach of the Longtail Shad are not found both types of food at once